LP decoding meets LP decoding: A connection between channel coding and compressed sensing - Dimakis, A.G.; Vontobel, P.O. (2009 47th Annual Allerton Conference on Communication, Control, and Computing, 2009)
This is a tale of two linear programming decoders, namely channel coding linear programming decoding (CC-LPD) and compressed sensing linear programming decoding (CS-LPD). So far, they have evolved quite independently. The aim of the present paper is to show that there is a tight connection between, on the one hand, CS-LPD based on a zero-one measurement matrix over the reals and, on the other hand, CC-LPD of the binary linear code that is obtained by viewing this measurement matrix as a binary parity-check matrix. This connection allows one to translate performance guarantees from one setup to the other.